Protective Effect of Ribes nigrum Extract against Blue Light-Induced Retinal Degeneration In Vitro and In Vivo - Chae Young Shin; Mun-Hoe Lee; Hyeong-Min Kim; Hee-Chul Chung; Do-Un Kim; Jin-Hee Lee; Kwang Won Jeong (Antioxidants, 2022)
Although blackcurrant has several health benefits, such as antioxidant and anti-inflammatory properties, its effects on the retina remain unclear. In this study, we investigated the efficacy of black currant extract (BCE) in an in vitro and in vivo model of dry age-related macular degeneration (AMD) induced by blue light. Dry macular degeneration is characterized by the abnormal accumulation of lipofuscin (e.g., N-retinylidene-N-retinylethanolamine, A2E) in the retina. Blue light (BL) significantly decreased the viability of A2E-laden human retinal pigment epithelial cells (ARPE-19). However, BCE treatment protected ARPE-19 cells from A2E and BL. A2E, which is oxidized by blue light, generates reactive oxygen species in RPE cells. Treatment with BCE significantly decreased (80.8%) reactive oxygen species levels induced by A2E and BL in a concentration-dependent manner. BCE inhibited A2E accumulation in ARPE-19 cells and significantly downregulated the expression of genes increased by A2E and BL in ARPE-19 cells. In vivo, oral administration of BCE (25–100 mg/kg) ameliorated ocular lesions of BL-induced retinal damage in a mouse model and rescued the thickness of the whole retina, photoreceptor segment layer, outer nuclear layer, and inner nuclear layer. The decrease in the number of nuclei in the outer nuclear layer induced by BL was also rescued by BCE. Additionally, BCE administration rescued (40.0%) the BL-induced reduction in the expression level of superoxide dismutase 1. Taken together, our results suggest that BCE may have preventive and therapeutic effects on dry AMD through its antioxidant activity and inhibition of lipofuscin accumulation in the retina.